Green synthesis of Cu2O@Ag core-shell nanocomposite with enhanced visible-light absorption. (15th September 2022) - Yuan, Binxia; Sun, Yongjun; Luo, Zige; Zhu, Rui; Luan, Weiling
Abstract: Cu2 O nanomaterials have a suitable band gap and high carrier mobility, but its stability and quantum yield are low. Through the research of scientists, it is found that the metal elements can help to improve the performance of Cu2 O nanomaterials. In the paper, the Cu2 O@Ag core-shell nanocomposite was quickly synthesized by hydrothermal method, and its method didn't need to use toxic solvents and additives. Trough XRD analysis, the obtained samples were composed of Cu2 O and Ag without other impurities. The valence band of Cu atom was Cu + rather than Cu 2+ and Cu 0 by XPS. The morphologies of pure Cu2 O and Cu2 O@Ag composites were all quasi spherical. Meantime, it was found that the size of Cu2 O@Ag was decreased with the increase of silver content. The reaction mechanism was also explained. Finally, the visible-light absorption and electrochemical impedance performance were investigated, which indicated the addition of Ag can increase the absorption range of visible light and reduce the impedance. Highlights: Cu2 O@Ag core-shell nanocomposite was quickly synthesized by hydrothermal method. The surface of Cu2 O was completely wrapped by Ag. The absorption performance of the Cu2 O@Ag was higher than that of pure Cu2 O. The impedance value decreased with the increase of silver content.